1994
DOI: 10.1021/ja00088a078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal and Molecular Structure of [{Hydroboratotris(3'-phenylpyrazolyl)}indium]: An Air-Stable Monomeric Indium(I) Complex

Abstract: As part of our work on the chemistry of the heavier members of group 13, we recently synthesized and structurally characterized [ bis(hydroboratotris(3,5-dimethylpyrazolyl)}indium(III)]iodide (2) and [bis(methylgallatotris(pyrazolyl))indium(III)]- [In141 (3).1 Recognizing the formal analogy between the hydroboratotrispyrazolyl anion HB(Pz)3-(and its pyrazolylsubstituted derivatives) and the cyclopentadienyl anions C5R5-(R = H, CH3),2 we were led to claim 2 and 3 as analogues of the unknown "indocene" cations [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Because bulky groups are known to stabilize a reduced In center, we attempted the reduction of 1 with Na/C 10 H 8 as shown in Scheme . The product of this reaction, 3 , possessed only the NMR resonances for equivalent dicyclohexylamidinate ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Because bulky groups are known to stabilize a reduced In center, we attempted the reduction of 1 with Na/C 10 H 8 as shown in Scheme . The product of this reaction, 3 , possessed only the NMR resonances for equivalent dicyclohexylamidinate ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrotris(3-phenylpyrazolyl)borate (Tp Ph ) has been utilized as a model for the active sites of various metalloenzymes (Kawabata et al, 1995;Halcrow et al, 1997;Perkinson et al, 1991;Kremer et al, 1997) and as a reagent for DNA binding and cleavage (Dhar et al, 2002). Tp Ph has also been used as a convenient scaffold for metal-mediated chemistry (Slugovc et al, 2000a;Darensbourg et al, 1996Darensbourg et al, , 2004Chisholm et al, 2000), for systematic 113 Cd chemical-shift studies (Reger et al, 1995), and for the synthesis of unusual compounds (Slugovc et al, 2000b;Frazer & Piggott, 1994; Multi-scan (SADABS; Bruker, 2002) Multi-scan (SADABS; Bruker, 2002) Multi-scan (SADABS; Bruker, 2002 Darensbourg et al, 1995Darensbourg et al, , 1996Siemer et al, 2001;Eichhorn & Armstrong, 1990). Although nickel(II) is biologically relevant and the similar compound [hydrotris(3-phenyl-5-methylpyrazolyl)borato](2,6-isopropylphenolato)nickel(II) was reported to have activity similar to 2,4,5-trihydoxyphenylalanine quinone cofactor (Deb et al, 2012), surprisingly, other than recently reported complexes with simple inorganic ligands (Frampton et al, 2015) 2.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications we drew attention to two significant features of some trispyrazolyl derivatives of group 13 [specifically HB(3-Bu t Pz) 3 2 and HB(3-PhPz) 3 2 ], namely their stabilisation of low oxidation states and their redox properties with main-group metals. 8,9 We now identify a third significant feature of a member of this class of ligand [specifically MeGa(pz) 3 2 ], viz. heterocubane formation.…”
mentioning
confidence: 99%